Bahasa Inggris - Kartika Chrysti Suryandari; Wahyudi; Rokhmaniyah; M. Chamdani; Dewi Indrapangastuti; Murwani Dewi Wijayanti (Postgraduate, University of Mataram, 2026)
The purpose of this research is: to describe the science learning experience in terms of creative thinking and to describe the level of students' ability to think creatively using the SRBP model. This study used Design-Based Research (DBR) to investigate the efficacy of hands-on experiments in science learning, combining qualitative and quantitative research methods. Participants were Elementary School Teacher Education students who had taken science lessons, with a total of 105 students. We have developed and examined how this approach might direct creative educational activities. This study uses the Scientific Reading-Based Project (SRBP) conceptual framework. Data collection techniques include questionnaires, observations, interviews, and student portfolios. The results showed that students' learning experience from the creativity aspect increased with each cycle. The learning participants' responses were enjoyable, stimulating students to think creatively. Students performed better because they learned and recalled information through practical experiences. This research recommends applying an innovative learning model that incorporates the principles of discovery and observation, which can stimulate students to think creatively.